Isolation and characterization of cellulose nanomaterials from jute bast fibers. Issue 6 (December 2021) - Dhali, Kingshuk; Daver, Fugen; Cass, Peter; Adhikari, Benu
Abstract: This work describes a simple yet effective pathway for extracting cellulose nanomaterials from jute bast fibers by chemical pretreatment to isolate microfibrillated cellulose followed by either mechanical or acid hydrolysis to ultimately isolate cellulose nanofibers (CNFs) and cellulose nanocrystals (CNCs), respectively. Analyses carried out through Fourier transform infrared spectroscopy (FTIR), X-ray photon spectroscopy (XPS) and solid state 13 C nuclear magnetic resonance (NMR) demonstrated that the pretreatments gradually removed lignins and hemicelluloses from the fibers. The yield of microfibrillated cellulose was 56.5% with respect to the initial dry mass of untreated fibers. Scanning electron microscopy (SEM) evaluated the morphological variation in the fiber dimension during the initial chemical pretreatment stages leading to extraction of microfibril 12–15 µm in average width. Transmission electron microscopy (TEM) images confirmed the nano-scale dimension of these nanocelluloses. The thermal stability of jute fibers at different stages of treatment was studied by thermogravimetric analysis. The high yield and high crystallinity of the nanocelluloses demonstrated effective isolation protocol confirming that jute bast fibers can be a valuable source for generation of nanomaterials. Graphical Abstract: ga1 Highlights: Highly purified microfibrillated cellulose was extracted with a yield of 56.5%. Cellulose nanofibers appeared like cylindrical fibrils with average diameter of 14.9 nm. Cellulose nanocrystals had an average width of 10.0 nm and a length of 196.5 nm. The yield of CNFs and CNCs from dry biomass was 55% and 28%, respectively. Crystallinity index for CNFs and CNCs were 67.5% and 75.6%, respectively.